Penerapan Metode Reward dalam Meningkatkan Kepercayaan Diri Siswa - Devi Ganjar Mustopa; Denisa Putri Herawati (Sekolah Tinggi Agama Islam Persatuan Umat Islam Majalengka, 2026)
Self-confidence is an important part of a person's personality development. With self-confidence, students will be able to evaluate their overall selves, which gives a strong belief in their abilities to take actions in achieving their desires. However, the self-confidence of fourth-grade students in SD Al-Hidayah Majalengka is still relatively low. One effort that can be used to increase students' self-confidence is the application of the reward method in the learning process. Based on the background, the problem formulation in this study is: how is the application of rewards to students? How is the self-confidence of the students? And does the application of the reward method improve the self-confidence of students in class IV C of Al-Hidayah Elementary School in Majalengka? This research aims to know the application of the reward method, to understand the students' self-confidence, and to assess whether the application of the reward method can enhance the self-confidence of students in class IV C at Al-Hidayah Elementary School, Majalengka. This type of research employs a Classroom Action Research design. In this PTK, there are 2 cycles, each consisting of 2 meetings. The subjects of this research are 19 students from class IV C. The data collection techniques in this research include observation sheets, interviews, and documentation. Data processing uses descriptive analysis.Based on the results of this study, it can be observed that the teacher's activity in applying the reward method has been implemented well. In Cycle I, the overall average teacher activity reached 76% with a fair category. Then in Cycle II, the overall average teacher activity increased to 81% with a good category. The observations of student activities indicate that overall, the results of the five student activities in Cycle I reached an average of 61% with a poor category. Then in Cycle II, the overall average of the five student activities increased to 85% with a good category. The initial observation before the implementation of the reward method showed that the confidence of the fourth-grade students of SD Al-Hidayah Majalengka was only 48% in the poor category. Furthermore , the results of the implementation of the reward method that has been carried out show that students' confidence in cycle I was 69% in the less good category, while the observation results of students' confidence in cycle II increased to 80% in the good category. Thus, it can be concluded that the reward method can improve students' confidence in class IV C at Al-Hidayah Elementary School Majalengka for the 2024-2025 academic year.